(untitled) (International Journal of Advanced Research in Computer Science, 2017)
MPEG standard is one of the most important standards for compressing video files, which is one of the most significant standards from ISO/IEC Company. For this standard, different parts are defined. We try to define four basic part of it that are MPEG1, MPEG2, MPEG3, and MPEG4. In this article, we glanced up at different standard in different part and also we provide a short brief for their usage of them. Â Keywords: Compression algorithm, ISO/IEC, MPEG, MPEG-1, MPEG-2, MPEG-3, MPEG-4